2001
DOI: 10.2527/2001.7971675x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GnRH pretreatment on reproductive performance of postpartum suckled beef cows following synchronization of estrus using GnRH and PGF2alpha.

Abstract: The effect of GnRH pretreatment on estrus detection rate, precision of estrus, and reproductive performance of postpartum beef cows synchronized to estrus using GnRH and PGF2alpha was evaluated. In Exp. 1, Angus cows (n = 87) were randomly assigned by parity, postpartum interval, and body condition score (BCS) to receive either 1) GnRH on d -7 and PGF2alpha on d 0 (GP) or 2) the GP treatment and an additional injection of GnRH on d -16 (GGP). Estrus detection and AI were conducted twice daily from d -3 to d 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…Moreover, recent studies in lactating beef cattle (Stevenson et al, 2000;DeJarnette et al, 2001a) and lactating dairy cows (Badinga et al, 1994) reported that the time of estrus after GnRH + PGF 2α treatment was approximately 60 h after PGF 2α . In another study, DeJarnette and Marshall (2003) reported that 65% of lactating dairy cows that were presynchronized with 2 PGF 2α injections (14 d apart) showed estrus on d 3 after the PGF 2α injection of Ovsynch, whereas none was observed in estrus before PGF 2α .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies in lactating beef cattle (Stevenson et al, 2000;DeJarnette et al, 2001a) and lactating dairy cows (Badinga et al, 1994) reported that the time of estrus after GnRH + PGF 2α treatment was approximately 60 h after PGF 2α . In another study, DeJarnette and Marshall (2003) reported that 65% of lactating dairy cows that were presynchronized with 2 PGF 2α injections (14 d apart) showed estrus on d 3 after the PGF 2α injection of Ovsynch, whereas none was observed in estrus before PGF 2α .…”
Section: Discussionmentioning
confidence: 99%
“…La tasa de ME en respuesta a la PGF 2α fue 67%, inferior a la señalada en vacas Holstein (76 a 89%; Ryan et al, 1995) y mayor a la obtenida en Angus (44%; DeJarnette et al, 2001). La ausencia de ME en algunas vacas podría atribuirse a que la PGF 2α no se aplicó en el momento óptimo para la luteólisis, la jerarquía social en el hato, calores silenciosos o fallas en DVE.…”
Section: Resultados Y Discusiónunclassified
“…Observation of oestrus and insemination requires labour and cows with synchronized oestrous cycles may exhibit oestrus prior to fixed‐time breeding associated with the protocol. Studies have reported that up to 72% of cows exhibit oestrus prior to or immediately after the PGF 2α administration (DeJarnette et al. 2001; Larson et al.…”
Section: Introductionmentioning
confidence: 99%